1993
DOI: 10.1007/bf01728886
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunization against cytomegalovirus in allograft recipients. The Rotterdam heart transplant program experience

Abstract: We analyzed the results of passive immunization against CMV in 146 heart transplant recipients. The 65 seronegative recipients were prophylactically treated with anti-CMV immunoglobulins during and after the operation. Twenty-nine of these 65 patients received a seropositive donor heart. CMV infection occurred in 21/65 seronegative and in 40/81 seropositive recipients (difference not significant). The incidence of CMV infection in seronegative recipients of a CMV-matched donor heart (3/34) was significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Initially, cytomegalovirus (CMV) seronegative recipients of the heart from a CMV seropositive donor (i.e., CMV mismatch) received passive immunization with anti‐CMV hyperimmunoglobulin during the first 72 days . From 2003 on, oral valganciclovir was prophylactically administered for 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, cytomegalovirus (CMV) seronegative recipients of the heart from a CMV seropositive donor (i.e., CMV mismatch) received passive immunization with anti‐CMV hyperimmunoglobulin during the first 72 days . From 2003 on, oral valganciclovir was prophylactically administered for 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…In the early phase of the program, CMV seronegative recipients of the heart of a seropositive donor received passive immunization with anti-CMV immunoglobulins (Cytotect; Biotest Pharma, Dreieich, Germany) during the first 72 days after transplantation ( 24 ). Later on, oral valganciclovir was prophylactically administered for 6 months (or longer in case of rejection treatment) in these CMV mismatched patients.…”
Section: Methodsmentioning
confidence: 99%
“…With the caveat that most of this supportive evidence derives from observational and or retrospective data analyses, several observational studies have shown that CMVIG treatment in heart transplantation is associated with a significant reduction not only in CMV infection, but also in graft-related outcomes, such as acute rejection and allograft vasculopathy. [61][62][63] Similarly, in the lung transplantation context, the combination of CMVIG with antiviral prophylaxis appears to provide additional protection against CMV disease, immune-mediated graft injury and CARV pneumonia. [64][65][66][67] Nevertheless, widespread utilization of CMVIG is limited by their cost and by the lack of confirmatory evidences from randomized studies.…”
Section: Hyperimmune Globulinsmentioning
confidence: 99%